Left atrial strain predicts fibrosis of left atrial appendage in patients with atrial fibrillation undergoing totally thoracoscopic ablation - Kim, Jihoon; Park, Sung-Ji; Jeong, Dong Seop; Chung, Suryeun; Jeon, Kina; Bak, Minjung; Kim, Darae; Kim, Eun Kyoung; Chang, Sung-A; Lee, Sang-Chol; Park, Seung Woo (Frontiers in Cardiovascular Medicine, 2023)
Background: Left atrial (LA) fibrosis is related with development and severity of atrial fibrillation (AF). The aim of this study was to investigated factors associated with LA fibrosis in patients undergoing totally thoracoscopic ablation (TTA) for AF. Methods: Between February 2012 and March 2015, a total of 128 patients who underwent TTA were enrolled from a tertiary hospital. Left atrial appendage (LAA) was harvested during surgery to determine the degree of fibrosis. LAA fibrosis was classified as mild (1st quartile), moderate (2nd and 3rd quartile), or severe (4th quartile). Clinical outcome was 5-year recurrence rate of AF detected on electrocardiogram or 24-hour Holter monitoring. Results: The mean age was 54.3 ± 8.8 years and 18.8% had paroxysmal AF. Patients with mild LAA fibrosis had a significantly lower rate of recurrent AF (23.3%) at 5 years after TTA compared with those with moderate (51.4%; hazard ratio [HR] 2.69; 95% confidence interval [CI] 1.19─6.12) or severe (53.2%; HR 2.84; 95% CI 1.16─6.97) fibrosis. Among clinical and echocardiographic parameters, peak LA strain was the only predictor of mild LAA fibrosis (coefficient 0.10, p=0.005) with the best cutoff value of 14.7% (area under the curve 0.732). The prevalence of mild LAA fibrosis was 40.6% in patients with peak LA strain ≥14.7%, but only 6.8% in those with peak LA strain <14.7%. Conclusions: In patients undergoing TTA for AF, mild LAA fibrosis was associated with a lower risk of 5-year AF recurrence. LA strain was the only predictor of mild LAA fibrosis that reflects a lower risk of 5-year AF recurrence.